W-Band Transverse Slotted Frequency Scanning Antenna for 6G Wireless Communication and Space Applications - Hurrem Ozpinar; Sinan Aksimsek; Nurhan Türker Tokan (Aerospace, 2025)
Terahertz (THz) antennas are among the critical components required for enabling the transition to sixth-generation (6G) wireless networks. Although research on THz antennas for 6G communication systems has garnered significant attention, a standardized antenna design has yet to be established. This study introduces the modeling of a full-metal transverse slotted waveguide antenna (TSWA) for 6G and beyond. The proposed antenna operates across the upper regions of the V-band and the entire W-band. Designed and simulated using widely adopted full-wave analysis tools, the antenna achieves a peak gain of 17 dBi and a total efficiency exceeding 90% within the band. Additionally, it exhibits pattern-reconfigurable capabilities, enabling main lobe beam steering between 5° and 68° with low side lobe levels. Simulations are conducted to assess the power handling capability (PHC) of the antenna, including both the peak (PPHC) and average (APHC) values. The results indicate that the antenna can handle 17 W of APHC within the W-band and 3.4 W across the 60–160 GHz range. Furthermore, corona discharge and multipaction analyses are performed to evaluate the antenna’s power handling performance under extreme operating conditions. These features make the proposed TSWA a strong candidate for high-performance space applications, 6G communication systems, and beyond.